(untitled) (European Journal of Multidisciplinary Studies, 2017)
Social impact assessment (SIA) is a process that provides a framework for gathering and analyzing information to determine intended and unintended social consequences of changes and developmental interventions on human environment. This assessment that emphasize on social and cultural issues, is more important in historic site that have more tangible social role than the new parts of the city and these areas should preserved by planning and subsequent evaluations due to their cultural heritage value. The aim of this paper that evaluated social impacts of reconstruction project of Jameh Mosque Street of Yazd city in Iran when it came into operation, is identify specific indicators for SIA in historic site through the use of general indicators and matching SIA process to the historical and cultural context of the heritage site. In order to achieve this goal, the research is based on SIA approach also descriptive and inferential statistics and focus group methodology were used to analyze the environment data. Hypotheses and measuring variables tested by analytic hierarchy process (AHP) and qualitative analysis with domain matrix. Accordingly, the estimation and selection of the effects of the project and its prioritization are based on some factors such as the importance and degree of feasibility that have different result in heritage site than the new urban areas. Finally, an operational framework and some strategic suggestions were made to improving the general process of SIA to use in heritage site and maximizing the efficiency of similar projects in every historic areas which leads to the consent of stakeholders.